2014
DOI: 10.1371/journal.pcbi.1003622
|View full text |Cite
|
Sign up to set email alerts
|

Slow Noise in the Period of a Biological Oscillator Underlies Gradual Trends and Abrupt Transitions in Phasic Relationships in Hybrid Neural Networks

Abstract: In order to study the ability of coupled neural oscillators to synchronize in the presence of intrinsic as opposed to synaptic noise, we constructed hybrid circuits consisting of one biological and one computational model neuron with reciprocal synaptic inhibition using the dynamic clamp. Uncoupled, both neurons fired periodic trains of action potentials. Most coupled circuits exhibited qualitative changes between one-to-one phase-locking with fairly constant phasic relationships and phase slipping with a cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 48 publications
0
17
0
Order By: Relevance
“…Moreover, the frequency may also fluctuate due to external input [21,22] or intrinsic noise [23], and the PRC may be frequency dependent [24]. Nevertheless, this conceptual framework for phase resetting is quite generally applicable to nonlinear oscillators.…”
Section: Phase-resettingmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the frequency may also fluctuate due to external input [21,22] or intrinsic noise [23], and the PRC may be frequency dependent [24]. Nevertheless, this conceptual framework for phase resetting is quite generally applicable to nonlinear oscillators.…”
Section: Phase-resettingmentioning
confidence: 99%
“…The phases of the velocity controlled oscillators (VCOs) will slip with respect to the reference oscillator. Phase resetting theory imposes the constraint that distinct oscillators must be functionally uncoupled to prevent locking [54] or sticking [23]. As they slip, the peak of each VCO will coincide with the reference oscillator each time a characteristic distance has been traversed in its preferred direction.…”
Section: Hippocampal Phase Codesmentioning
confidence: 99%
“…Moreover, based on the shape of the PRC, the magnitude of change in phase is large when phase is away from 0 and 1, such that spiking is asynchronous, and small when the phase of is nearly synchronous. As a result, the network remains close to synchrony most of the time but with approximately periodic asynchronous excursions, a phenomenon referred to as phase slipping ( Thounaojam et al, 2014 ). The frequency of phase slipping is determined by the number of stimulus kicks needed for the phase to progress through one full cycle, which in turn is determined by the shape of the PRC.…”
Section: Resultsmentioning
confidence: 99%
“…To reconcile the differences between intracellular vs. intercellular heterogeneity, we postulate that the intrinsic properties of the CA1 hippocampal cells, and hence their PRCs, might be slowly changing throughout each trial. Another recent study (Thounaojam et al, 2014 ) suggested that the natural frequencies of periodically firing neurons can drift over time. A methodology that explicitly accounts for uncertainty in the PRCs across time can help ensure entrainment over the entire duration of the experiment.…”
Section: Discussionmentioning
confidence: 99%